Aplicação do ecodesign em empresa mineira e a percepção dos funcionários: um estudo de caso - Ana Paula Venturini Bandeira (2003)
The manufacturing industry has one of the greatest responsibilities forenvironmental degradation, due in part to the great quantity of inadequately treated pollutant emissions and residues created as a byproduct of the manufacturing process. Also additional, secondary pollution, is caused by a lack of correct environmentally focused designs considering the products overall life cycle. Considering theserelationships, this dissertations main objective is to gauge the manufacturing industries current perception of the importance of environmentally related variables over the product development process. This search and evaluation is achieved through questionnaires directed at environmental design factors and completed by a leading Brazilian manufacturing company. The target company was chosen as it currently has an advanced center for product development, making it a receptive to this type of study. This search intends to prove that it is possible to use product development tools and methodologies with environmental variables being a key to the process from conception. The dissertation also shows, through lecture revision, ways to insert these variables into the engineering process using principles similar to those developed during the 1980s quality control era. The analysis shows that great, ecologically sound results are achieved through systematic application of these environmental project tools.